Relationship Between the Use of Pantyliners and Feminine Cleansing Soap on the Incidence of Leucorrhea Among Women of Reproductive Age in Kebon Jeruk Village, Bandar Lampung, Indonesia - Ana Mariza; Sunarsih Sunarsih; Susilawati Susilawati (Poltekkes Kemenkes Palu, 2026)
Background: Leucorrhea (vaginal discharge) is not a disease itself but a clinical manifestation of various gynecological conditions. It is reported that approximately 90% of cervical cancer cases are accompanied by leucorrhea. A preliminary survey conducted in July 2024 in Kebon Jeruk Village, Bandar Lampung, found that 205 out of 345 women of reproductive age experienced symptoms of leucorrhea. Inappropriate genital hygiene practices, including frequent use of pantyliners and feminine cleansing soap, are suspected risk factors for this condition. Methods: This study employed a quantitative cross-sectional design. The study population consisted of 345 women of reproductive age, with 205 participants selected using purposive sampling. Data were collected through structured interviews using validated questionnaires. Bivariate analysis was performed using the chi-square test. Ethical approval was obtained from the Health Research Ethics Commission (No. 4557/EC/KEPP-UNMAL/IX/2024) Results: The results showed a statistically significant association between frequent pantyliner use and the incidence of leucorrhea (p = 0.007; OR = 5.098). Similarly, frequent use of feminine cleansing soap was significantly associated with leucorrhea (p < 0.001; OR = 4.203). Women who frequently used pantyliners and feminine cleansing soap had a higher likelihood of experiencing leucorrhea compared to those who did not use these products. Conclusion: Frequent use of pantyliners and feminine cleansing soap is significantly associated with an increased incidence of leucorrhea among women of reproductive age. Health education programs should emphasize appropriate genital hygiene practices and discourage excessive use of pantyliners. Carrying spare underwear is recommended as a safer alternative to routine pantyliner use to reduce the risk of leucorrhea.